Geoestatística e atributos do solo em áreas cultivadas com cana-de-açúcar - Souza, Zigomar Menezes De; Marques Júnior, José [UNESP]; Pereira, Gener Tadeu [UNESP] (Universidade Federal de Santa Maria, 2010)
The intense traffic of agricultural machines in soils cultivated with sugar cane can cause soil compaction. Therefore, the objective of this research was to characterize the spatial variability of soil physical attributes and content organic matter of a eutroferric Red Latosol gibbisitic (under Basalt) and dystroferric Red Latosol caulinitic (under Sandstone) in the depths of 0.0-0.2m and 0.2-0.4m in areas cultivated with sugar cane. Soils were sampled at the crossing points of a grid at regular intervals of 10m and at depths of 0.0-0.2m and 0.2-0.4m. Bulk density, macroporosity, organic matter content and soil penetration resistance were measured for all sampling points. The physical attributes show values of soil penetration resistance, bulk density and macroporosity above average for these soils. The studied variable presented a larger range and minor variation coefficient in the eutroferric Red Latosol (Oxisol Eutrustox) when compared with the dystroferric Red Latosol (Oxisol Haplustox), in the studied depths. It is recommended a bigger number of samples to study the eutroferric Red Latosol attributes and the depth of 0.2-0.4m.

Em solos sob cultivo de cana-de-açúcar, o tráfego intenso de máquinas agrícolas pode provocar estado de compactação ao solo. Portanto, o objetivo deste trabalho foi caracterizar a variabilidade espacial de atributos físicos e teor de matéria orgânica de um Latossolo Vermelho eutroférrico gibbsítico (sob Basalto) e Latossolo Vermelho distroférrico caulinítico (sob Arenito) nas profundidades de 0,0-0,2m e 0,2-0,4m, em áreas sob cultivo de cana-de-açúcar. Os solos foram amostrados nos pontos de cruzamento de uma malha, com intervalos regulares de 10m, nas profundidades de 0,0-0,2m e 0,2-0,4m, totalizando 100 pontos para cada área de estudo. Em cada ponto da malha, foram determinados a densidade do solo, a macroporosidade, o teor de matéria orgânica e a resistência do solo à penetração. Os atributos físicos mostram valores de resistência do solo à penetração, da densidade do solo e da macroporosidade acima da média para esses solos. As variáveis em estudo apresentaram um maior alcance e menor coeficiente de variação no LVef em comparação com o LVd, nas profundidades em estudo. Recomenda-se maior número de amostragem para os atributos em estudo no Latossolo Vermelho distrófico e na profundidade de 0,2-0,4m.
Geostatistics and soil attributes in area cultivated with sugar cane
Keywords: Saccharum offcinarum; spatial variability; oxisol; Saccharum offcinarum; variabilidade espacial; latossolos